Elevated systemic microbial translocation in pregnant HIV-infected women compared to HIV-uninfected women, and its inverse correlations with plasma progesterone levels. (June 2018) - Zhou, Zejun; Powell, Anna Maya; Ramakrishnan, Vishwanathan; Eckard, Allison; Wagner, Carol; Jiang, Wei
Abstract: In HIV infection, increased adverse perinatal outcomes reported among HIV-associated pregnancies are not fully understood. Currently, microbial product translocation (MT) from a permeable mucosa is demonstrated as a driver of inflammation, and may contribute to preterm delivery in HIV. Here, our results showed that plasma LPS levels (a representative marker of MT) were increased in HIV-infected women in the first and second trimester. Progesterone levels were significantly decreased in HIV-infected subjects in the first trimester and second trimester. There were significant inverse correlations between plasma LPS and progesterone in the first and second trimester. These results suggested heightened systemic MT and decreased plasma progesterone levels in HIV-infected pregnant women may play a role in increased incidence of preterm delivery.